Associations of HIV testing with anxiety and stress within the African American church: implications for faith-based HIV testing and treatment - Stewart, Jennifer (Mental health, religion & culture, 2017)
The promotion of HIV testing among Black Americans is critical to reducing disproportionately high rates of HIV and AIDS. Anxiety and stress are often found to be associated with resistance to HIV testing. The Black Church, may have an important role in reducing stress and anxiety associated with HIV testing. In this cross-sectional survey-based study, we compared the responses of the congregants from two churches which offered testing and two which did not (n = 177). Data were analysed with descriptive statistics, Chi-square test, and multivariate logistic regression. We found that in churches without HIV testing, HIV-associated anxiety was significantly higher (OR = 4.60, p < .001; 95%CI: 2.03, 10.41) as were levels of stress (OR = 6.87, p < .001; 95%CI: 2.69, 17.56). These results suggest that churches willing to incorporate HIV testing may have profound impacts on destigmatising HIV testing and treatment.